Funga poroide da guarnição da aeronáutica de Pirassununga (São Paulo, Brasil) - Giovanini, Mario (2022)
Poroid fungi are a group of major ecological importance given their capacity of breaking down wood. Through their activity, they play an important role in nutrient cycling and ecosystem maintenance, especially in forests. In spite of their importance, they, as are fungi in general, are underrepresented in studies, and their diversity and distribution remain fairly unknown. It's Important that further inventory studies on the group are carried out, given their ecological role and the dependency of conservation efforts on diversity studies. This study aimed at surveying poroid fungi diversity in different woodland formations as well as human-occupied areas of PirassunungaAirforce Base, an important area for conservation studies that holds unsurveyed native vegetation fragments. Being the first of its type done in the area, this study produced important data regarding the diversity of poroid fungi in the area, and samples collected are being cataloged and will be deposited in collections. In total, 46 specimens were collected, of which 42 were identified,representing 14 species and 2 morphospecies, representing eight distinct families. An identification key as well as a Field Guide were produced as the results of the project.